Phylogenetic position of the fish genera Lobotes, Datnioides and Hapalogenys, with a reappraisal of acanthuriform composition and relationships based on adult and larval morphology - Gill, Anthony C.; Leis, Jeffrey M. (Zootaxa, 2019)
Lobotes, Datnioides and Hapalogenys are assigned to a newly defined Acanthuriformes on the basis of their pattern of tooth replacement (termed posterolateral tooth replacement), where new teeth form at the posterolateral ends of series. Posterolateral tooth replacement is shown to be a synamorphy of the order. The order is expanded to include Chaetodontidae, Pomacanthidae, Drepaneidae, Ephippidae, Leiognathidae, Antigonia, Scatophagidae and Capros, along with the more traditional members, Siganidae, Luvaridae, Zanclidae and Acanthuridae. Three-item analysis of 63 adult and larval morphological characters yields two optimal trees that differ only in the relative positions of Capros and Siganidae. The intersection tree of the two optimal trees is: (((Hapalogenys (Datnioides, Lobotidae)) (Pomacanthidae (Drepaneidae (Chaetodontidae (Ephippidae (Leiognathidae (Scatophagidae (Antigonia (Siganidae, Capros (Luvaridae (Zanclidae, Acanthuridae)))))))))))). This cladogram is compared with recent phylogenies based on analyses of sequence data, and few differences are found once the weakly-supported interior nodes of the latter are collapsed. Aside from expansion of the Acanthuriformes, the following classification changes are proposed in order to reflect the phylogenetic relationships: redefinition of the Lobotidae to include Lobotes, Datnioides and Hapalogenys; separate families for Antigonia and Capros (Antigoniidae and Caproidae, respectively); continued recognition of Drepaneidae (often considered a synonym of Ephippidae). The larvae of Capros aper are illustrated to show features overlooked in earlier descriptions.